Parental expectations for young people's participation in higher education in Australia. Issue 2 (1st February 2019) - Koshy, Paul; Dockery, Alfred Michael; Seymour, Richard
ABSTRACT: This paper examines factors affecting parental expectations of higher education prospects for their children using Australian household survey data. We find that a variety of factors influence parental expectations, of which parents' assessment of their children's academic performance is the strongest. Factors known to impact upon actual higher education participation, such as parental education and remoteness, are already evident in parental expectations, but with limited evidence of expectations being shaped by financial constraints. We also find evidence of a 'same gender' effect, with mothers exhibiting higher expectations for higher education for their daughters. This may be in part due to significantly lower expectations held by fathers with sub-bachelor qualifications. These factors contribute to higher expectations overall for girls entering university. The research points to the importance of interventions commencing in early childhood, and accounting for key household background characteristics when designing, implementing and evaluating programmes for widening participation in higher education.